Hydrothermal vents as a kinetically stable source of iron-sulphide-bearing nanoparticles to the ocean - Yucel, M; Gartman, A; Chan, Clara S; Luther, G W (Nature Geoscience, 2011)
Hydrothermal vents emit sulphur and metals to the ocean(1). Particular attention has been paid to hydrothermal fluxes of iron(2-4), a limiting micronutrient of marine primary production(5). Vent-derived iron was previously thought to rapidly oxidize and precipitate around vents(6). However, organic matter can bind to and stabilize dissolved and particulate iron in hydrothermal plumes(7-9), facilitating its dispersion into the open ocean(10). Here, we report measurements of the chemical speciation of sulphide and iron in high-temperature fluids emanating from vents in the East Pacific Rise and the Eastern Lau Spreading Center. We show that pyrite nanoparticles-composed of iron and sulphur-account for up to 10{%} of the filterable iron (less than 200nm in size) in these fluids. We suggest that these particles form before the discharge of the vent fluid. We estimate that pyrite nanoparticles sink more slowly than larger plume particles, and are more resistant to oxidation than dissolved Fe(II) and FeS. We suggest that the discharge of iron in the form of pyrite nanoparticles increases the probability that vent-derived iron will be transported over long distances in the deep ocean.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)